2002
DOI: 10.1111/1467-9566.00316
|View full text |Cite
|
Sign up to set email alerts
|

‘Everybody just freezes. Everybody is just embarrassed’: felt and enacted stigma among parents of children with high functioning autism

Abstract: This paper reports the results of a study of felt and enacted stigma among a sample of parents of children with high functioning autism. The results indicate that a majority of the parents experienced both types of stigma, but that mothers were more likely to do so than fathers. This was especially true in the case of enacted stigma, where a majority of mothers, but only a minority of fathers, encountered avoidance, hostile staring and rude comments from others. The child's type of autistic symptoms was also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
325
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(358 citation statements)
references
References 16 publications
20
325
0
13
Order By: Relevance
“…These findings are consistent with other studies (i.e. Gray, 1993;Gray, 2002;Green, 2003;Green et al, 2005;Broady et al, 2015;Kinnear et al, 2016) that indicated the majority of parents experienced felt stigma. Stigma certainly plays a major and significant role in making lives difficult for parents of children with ASD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with other studies (i.e. Gray, 1993;Gray, 2002;Green, 2003;Green et al, 2005;Broady et al, 2015;Kinnear et al, 2016) that indicated the majority of parents experienced felt stigma. Stigma certainly plays a major and significant role in making lives difficult for parents of children with ASD.…”
Section: Discussionsupporting
confidence: 93%
“…Gray, 2002;Hutton and Caron, 2005;Montes and Halterman, 2007;Tomanik, Harris and Hawkins, 2004) has discussed the difficulties that parents of children with ASD often face in their daily lives. Glover-Graf (2011), for instance, postulates that parents of children with ASD are likely to experience strained marital and extended family relationships, social isolation, challenging educational arrangements, and a sense of grief related to the restricted opportunities for their children.…”
Section: Autism In the Greek Educational Contextmentioning
confidence: 99%
“…al. 2005) and helps us to comprehend the experience of mothers of children diagnosed with autism (see Gray 1993Gray , 2002.…”
Section: Stigmatising Mothers-from Courtesy To Attachment Stigmamentioning
confidence: 99%
“…In Australia, David Gray (1993Gray ( , 2002 has studied courtesy stigma amongst parents of children diagnosed with autism. He argues that mothers usually feel more stigmatised than fathers, in part because they 'take greater responsibility for the public presentation of the family' (Gray 1993, p.114) in fulfilling 'the traditional role of primary caregiver' (Gray 2002, p.743).…”
Section: Theorising Prolonged Dependency: Developmental Disability Anmentioning
confidence: 99%
“…Internationally, Autism Spectrum Disorder (ASD) is the fastest growing developmental disability [5], creating significant challenges for educational, health and social care services [4,16], as well as for families and individuals (e.g. [7,9,10,12]). The increasing prevalence of autism is recognised as a global health priority [20], with WHO member nations being urged to prioritise the needs of individuals with autism and their families and communities through increasing research in service provision in order to improve available support.…”
Section: Introductionmentioning
confidence: 99%